Phonology Acquisition For Children Aged 4-4.4 Years At Paud Smart Parahyangan - Fenny Anita; Neni Triana; Noprieka Suriadiman (STKIP ROKANIA, 2022)
Language acquisition, especially phonological acquisition, has started since children acquire their first language (mother tongue). Language acquisition at the phonological level by children also does not just happen without the influence of the environment. Sound acquisition by children aged 4 years in this study only focused on the sounds of nouns and verbs that have been obtained by children. The focus of the study in this research is the acquisition of phonology by children aged 4-4.4 years in terms of phonetics. The purpose of this study was to describe the sounds obtained by children aged 4-4.4 years. This type of research is a qualitative research with descriptive method. The data of this research are the sounds spoken by the research object. The subjects of this study were children from Paud Smart Parahyangan which consisted of one person. The subject of this research is Muhammad Adam. The data collection technique in this study is a naturalistic technique. First, the acquisition of the phonology of children aged 4 years, especially Adam, has not been able to pronounce the sound [r] perfectly. This can be seen from the pronunciation of the sound [r] in the sound of the words [silsa?], [dulian], [lambutan], [jelu?], and [bεlajal] which still sound like the sound [l]. In addition, Adam also has not been able to pronounce the sound [ŋ]. The sound is clearly heard when he pronounces the sound [ŋ] on the sound of the word [manaŋih] “crying” which still sounds like the sound [ñ]. Second, the acquisition of phonology for children aged 4 years 4 months, Adam has been able to master the sound [r] and sound [ŋ] which he had not previously mastered.